Energy analysis in dairies of the Argentina Pampa´s region. Part 1. Energy flows - Gimenez, Gustavo Daniel; Novaira, Bruno Idelfonso; Marini, Pablo Roberto (Agronomía Mesoamericana, 2022)
Introduction. The heterogeneity of agricultural systems makes it difficult to assess their sustainability, since there are no tools that can be applied to most cases, with indicators that are easily understood by the stakeholders in the field. One possible tool for use is energy analysis. Objectives. To contextualize the heterogeneity of primary milk production models, based on energy flowcharts. Materials and methods. A retrospective data from nine commercial milk production establishments in the Argentine Pampas Region, during the period from July 2014 to June 2015 were worked with. These were differentiated according to variables such as animal stocking rate and level of feed supplementation. The case study methodology was used, with energy analysis for each case, configuring flowcharts for each one, and quantifying inputs, outputs, and energy use efficiency. Results. The existence of three systems was determined: mixed dairy-agricultural with fattening, mixed dairy-agricultural, and pure dairy with fattening. The mixed systems are important, due to the energy flow provided by agriculture to compensate for the significant energy loss of the milk and meat subsystems; however, the purely livestock systems turned out to be more efficient in energy use, due to lower energy consumption and forage production. Conclusions. The energy analysis was useful to characterize the heterogeneity between systems through the construction of flow charts. It also allowed evaluating social and environmental aspects, which in traditional analyzes are excluded; but which, given the volume of energy flow they provide, motivate the need to include them in accounting due to their importance for the dairy process and due to the close link between nature and society, associated with the man-ecosystem complex.